EFFEKTIVNOST' VNUTRISUSTAVNOGO VVEDENIYa GENTAMITsINA PRI PODAGRIChESKOM ARTRITE - A. V. Orlov-Morozov; E A Dolzikova; E A Orlova-Morozova; N G Berdnikova; T Ya Selezneva; E V Tkachenko; R I Elagin (Научно-практическая ревматология)
Aim: То determine the efficacy of intraarticular injections of Gentamycin in gout arthtiris a randomized double blind, placebo-controlled trial was carried out. Material and methods: 27 patients answering the criteria of the definite gout diagnosis were randomly recruited from rheumatological clinic. The patients received an intraarticular injection of either 4- mg of Gentamycin in 4 ml of sterile 0.25% procaine or 5 ml of the vehicle alone. Results: It was found that weekly intraarticular injections of Gentamycin performed better than the inert vehicle alone over a 2-week period and were conjirmed during 4 week period of crossing-over. Conclusion: The possible mechanisms of Gentamycin activity are discussed. It is concluded, that intraarticular administration of Gentamicin offers signijicant benejit over placebo. The serious side effects were not obsen’ed. Therefore, the technique could be applied in the routine treatment of gout.